Approaching sustainability and circularity along waste management systems in universities: an overview and proposal of good practices - Giurea, Ramona; Carnevale Miino, Marco; Torretta, Vincenzo; Rada, Elena Cristina (Frontiers in Environmental Science, 2024)
In recent years, the importance of sustainability and circularity in waste management systems has become increasingly evident. As the world grapples with the environmental consequences of excessive waste generation, it has become crucial to find innovative and sustainable solutions. Universities, as centres of knowledge and research, play a vital role in achieving sustainability and circularity in waste management. The key contribution of this study is to provide: (1) a systematic review of the existing literature concerning sustainable waste management systems (SWMS) implemented in universities; (2) an analysis of the studies presented in this paper identifying applicable approaches and sustainable practices to provide novel guidelines by including waste management system in a circular and sustainable model within universities. Through research, collaboration, education, implementation of sustainable practices, and support for entrepreneurship, universities can strongly contribute to the development and implementation of sustainable waste management practices. As the world continues to face the challenges of waste generation, universities will continue to be at the forefront of finding innovative, sustainable, and circular solutions. Formatted: Italian Deleted: matter 40 Deleted: SDG12 41 Deleted: Universities have a significant role to play in achieving 42 sustainability and circularity along waste management systems.